IMPACT ANALYSIS OF LOSS INDUSTRIAL SECTOR AT PT PERTAMINA PERSERO - Devita Herlin Putri Restia; Fadilla Jannati; M. Gilang Tri Atmaja; Fera Wati; Bella Anggun Riskita; Husna Angel (CV. Era Digital Nusantara, 2023)
The Covid-19 pandemic hampered the company's cash flow and reduced public demand for fuel oil, natural gas, geothermal energy at PT Pertamina Persero that year. It was noted that in 2020 PT Pertamina Persero experienced a rapid decline which resulted in losses. This has an influence on the profit earned by PT Pertamina. This study aims to describe the factors that caused PT Pertamina to experience losses, describe the losses experienced, and describe the role of commissioners in the losses that occurred at PT Pertamina. This research uses the literature study method, this is done because literature sources are obtained from journals, information from print media, research reports, articles, and other sources. The approach in this study uses descriptive qualitative, with the aim of describing and disclosing the phenomena that occur in depth and systematically. Pertamina's losses were caused by the pandemic (Covid-19) and the decline in operating income due to the sale of crude oil, natural gas, heat energy and oil production is experiencing a decline. The Role of the Board of Commissioners Against PT Pertamina's Losses, The Board's duty is to examine the competence of the Company and management, management usually pays attention to the Company and its business activities, advises managers on the company's income. In carrying out the supervisory duties of the board of commissioners and in preparing plans for the benefit of the company,